2017
DOI: 10.3389/fnmol.2017.00175
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Pannexin-1 Channels in Inflammatory Response through the TLRs/NF-Kappa B Signaling Pathway Following Experimental Subarachnoid Hemorrhage in Rats

Abstract: Background: Accumulating evidence suggests that neuroinflammation plays a critical role in early brain injury after subarachnoid hemorrhage (SAH). Pannexin-1 channels, as a member of gap junction proteins located on the plasma membrane, releases ATP, ions, second messengers, neurotransmitters, and molecules up to 1 kD into the extracellular space, when activated. Previous studies identified that the opening of Pannexin-1 channels is essential for cellular migration, apoptosis and especially inflammation, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…While Panx1 is a direct target of NFκβ activation, we further demonstrate that Panx1 signaling can enhance NFκβ activation. This is in keeping with studies by Wu et al that pointed to a role of Panx1 in the control of NFκβ activation (Wu et al, 2017). Our data highlight that TNF induces an increase in P-p65 activation, that is significantly reduced when Panx1 expression is knocked down by siRNA and when the channel is blocked in the presence of the PxIL2P peptide.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While Panx1 is a direct target of NFκβ activation, we further demonstrate that Panx1 signaling can enhance NFκβ activation. This is in keeping with studies by Wu et al that pointed to a role of Panx1 in the control of NFκβ activation (Wu et al, 2017). Our data highlight that TNF induces an increase in P-p65 activation, that is significantly reduced when Panx1 expression is knocked down by siRNA and when the channel is blocked in the presence of the PxIL2P peptide.…”
Section: Discussionsupporting
confidence: 92%
“…ATP release through Panx1 channels has been shown to be a strong signal for the recruitment of inflammatory cells in response to apoptosis (Chekeni et al, 2010) and activation of the NLR3P inflammasome (Albalawi et al, 2017; Lappas, 2014; Wu et al, 2017). However, the precise Panx1-mediated mechanisms controlling inflammation have never been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of the LPS/TLR4/NF-kB pathway in the anti-inflammatory immune response, a number of studies have focused on its underlying mechanism. At present, research on TLR/NF-κB has mainly focused on the identification of TLR structure, the regulation mechanism of NF-κB activation and the nature of TLR-oriented anti-infective drugs (30,31). The present study focused on the regulatory mechanism of NF-κB activation and observed that this involved the generation of cellular ROS.…”
Section: Discussionmentioning
confidence: 73%
“…Pannexin-1 channels, a member of gap junction proteins involved in the innate and acquired immune system, could also contribute to the induction of inflammation and cognitive dysfunction of SAH via the TLR2/TLR4/NF-κB-mediated signaling pathways. Pannexin-1 channels protein gene knockdown significantly reduced the expression values of TLR2/4/ NF-κB signaling pathway in the neocortex and improved cognitive and memory deficits in a rat SAH model [143].…”
Section: The Role Of Toll-like Receptors In Subarrachnoid Hemorrhagementioning
confidence: 90%